The effectiveness of al-Rahn (Islamic pawn broking scheme) on socio-economic needs - Mohd Noar, Nor Zaihan; Ahmad, Norsita Lin (Revelation and Science, IIUM, 2015)
This paper aims to identify the effectiveness of al-Rahn, an Islamic pawn broking scheme, on socio-economic needs. The primary research fieldwork was conducted in Kuala Terengganu, Terengganu and Kuantan, Pahang. Semi-structured questionnaires were used to collect data and were analyzed via the cross tabulation using excel spreadsheet. The findings from this study implies that the community, especially the Malay ethnicity, found al-Rahn to be able to fulfill their needs for fast and hassle free, small short term loans, hence providing loyalty to the scheme. The need for fulfillment is derived from data collected from two main components of al-Rahn i.e. loan tenure and loan sufficiency. While al-Rahn services are currently growing in popularity and offered by many institutions, the al-Rahn institutions used under this study is limited to Kuantan and Kuala Terengganu towns.